Thoracoscopic stapler-closure of left atrial appendage and epicardial clamp-isolation of pulmonary veins in a patient with non-valvular atrial fibrillation and short bowel: a case report - Ohtsuka, Toshiya (Eur Heart J Case Rep, 2019)
BACKGROUND: Thromboembolic occlusion of the superior mesenteric artery (SMA) is a serious event in patients with atrial fibrillation (AF). Extensive bowel resection is frequently required, and the resulting short bowel syndrome hampers the intake of anticoagulant or anti-arrhythmic medication. CASE SUMMARY: We report the case of thoracoscopic surgery consisting of stapler-closure of the left atrial appendage and bilateral epicardial clamp-isolation of the pulmonary veins performed in a 66-year-old male patient with symptomatic persistent non-valvular AF who became unable to take in anticoagulants or anti-arrhythmic drugs because of thromboembolic SMA occlusion and subsequent total resection of the small intestine. The patient has been free from thromboembolic or arrhythmic symptoms during 6 months of follow-up despite taking no anticoagulant or anti-arrhythmic drugs. Electrocardiographic monitoring demonstrated a stable sinus rhythm for 48 h at postoperative Months 3 and 6. Echocardiography manifested an improvement of the left ventricular ejection fraction from a preoperative value of 44–69% at postoperative Month 6. DISCUSSION: The present technique may contribute to treating patients with symptomatic non-valvular AF and a complication similar to that of the present case.